Halide perovskite solar cells: an investigation of ink additives on perovskite crystallization - Choong, Anthony Li Yan (Nanyang Technological University, 2022)
Perovskite solar cells (PSCs) are among the 3rd generation of solar cells which can compete with the conventional bulk silicon solar cells in terms of power conversion efficiency (PCE). They have been hotly researched over the past decade, with their high absorption coefficients, tunable band gaps and inexpensive facile fabrication processes as the main selling points. In just 13 years since the first PSC was successfully synthesised, the PCE has skyrocketed from 3.8% in 2009 to 25.8% (25.5% certified) in 2021, with plenty of research and keen interest ongoing to improve device performance; and also to achieve the ultimate goal of commercialising PSCs. However, the main drawback of PSCs is their poor stability in the ambient environment, which is well-documented and adversely impacts efforts to commercialise PSCs. The stability of PSCs has been the subject of numerous studies by many researchers who seek to prolong the stability of PSCs besides improving their PCE.